Measuring community power - Ashley Gripper; Tori Cowger (Journal of Agriculture, Food Systems, and Community Development)
Participation in community farming and gardening increases and improves social support, collective agency, care, and resistance in many historically exploited communities. Black- and Brown-led food justice organizations have expressed the need for an instrument that captures what is most important to them: information on how their programs impact land-based knowledge, spirituality, collective agency, resistance, and mental health. This study used a survey instrument to develop a scale using exploratory factor analysis. Participants were recruited with the help of key partners and influencers from U.S.-based agricultural networks. The final analyzable sample contained 363 respondents. The scree plot, parallel test, and eigenvalues all supported a five-factor structure as most appropriate for the data. These five inter-related factors explain a concept called “Agricultural Community Power” and refer to Collective Self-determination, BodyMind Community Care, Land-based Spiritual Wellbeing, Embodied Earth Care and Connection, and Ubuntu/Interdependence. This model had adequate internal consistency reliability (Cronbach’s alpha = 0.93). The Agriculture Community Power Scale (AgCPS) is a tool that (1) can be used for program evaluation and (2) is better aligned with the values, priorities, and impacts of many community-rooted environmental organizations. AgCPS moves food justice evaluation away from standard metrics (such as BMI and fruit and vegetable consumption) and toward metrics of community care, collective agency, land-based spirituality, and community power.